(untitled) (Journal of Computational Mathematics, 1987)
The cardinalities of interpolating restricted range R_1(m,n) for best rational approximation are discussed. The conditions under which the cardinality of R_1(m,n) is 0 or 1 or ∞ are established by using the results obtained in [3,4].